OUTCOMES OF RECONSTRUCTION WITH VASCULARIZED VS NON-VASCULARIZED BONE GRAFT AFTER RESECTION OF BONE TUMOURS- A SYSTEMATIC REVIEW AND META-ANALYSIS - Ali, Sheikh Muhammad Ebad; Razak, Sufyan; Khan, Wajiha Fatima; Khan, Shiza; Khaimchandani, Devya; Akhtar, Umme Roman; Badaruddin Sahito; Abbasi, Ahmed Nadeem (Journal of Ayub Medical College Abbottabad, 2023)
Background: Vascularized (VBG) and non-vascularized (NVBG) bone grafting are two crucial biological reconstructive techniques in the management of bone tumours. The objective of this study is to compare the outcomes of reconstruction with vascularized and non-vascularized bone grafts after resection of bone tumours. Methods: A systematic evaluation of the literature from 2012-2021 was undertaken using the online databases PubMed/Medline, Google Scholar, and Cochrane Library considering only comparative articles with specific outcomes for the restoration of the defect with vascularized and non-vascularized bone graft following the resection of bone tumours. The quality of the research methodology was evaluated using Oxford Quality Scoring System and Newcastle Ottawa Scale for randomized trials and non-randomized comparison research respectively. The SPSS version 23 was used to examine the data that was collected. Musculoskeletal tumour society score (MSTS), bone union time, and complications were the outcomes of this review. Results: Four clinical publications were considered, totalling 178 participants (92 men and 86 women) with 90 patients with VBG and 88 with NVBG. MSTS score and bone union time were the key outcomes that were measured. The overall MSTS (p>0.05) and rate of complications (p>0.05) results were comparable between the two groups, however, VBG had a better rate of bone union (p<0.001). Conclusion: As a result of the quicker bone union, our systematic evaluation demonstrated that VBG causes earlier recovery. Complication rates and functional results were the same in both groups. The link between the bone union time and functional score following VBG and NVBG must also be demonstrated.